1990
DOI: 10.1002/jmv.1890320107
|View full text |Cite
|
Sign up to set email alerts
|

Antibody responses against polypeptide components of Epstein‐Barr virus‐induced early diffuse antigen in patients with connective tissue diseases

Abstract: The specific humoral response against polypeptide components of Epstein-Barr virus (EBV), the induced early diffuse antigen (EA-D), in patients with connective tissue diseases, including systemic lupus erythematosus (SLE) and mixed connective tissue disease (MCTD), was investigated by using the immunoblotting technique. The EA(D)-positive sera from patients with infectious mononucleosis (IM), nasopharyngeal carcinoma (NPC), immunocompromised patients (renal transplant recipients and patients with AIDS) as well… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
15
0

Year Published

1991
1991
2010
2010

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 39 publications
1
15
0
Order By: Relevance
“…In SLE, 238 Tsai/Chiang/Kao/Hsieh Epstein-Barr Virus and Systemic Lupus erythematosus polyclonal B activation might play an important role in the pathogenic mechanism of the disease process, and abnor mal expansion of the autoreactive B cell population induced by viral infection like EBV might lead to autoimmune reac tions. Antibodies against specific EBV nuclear antigens have been related to certain autoimmune diseases such as rheumatoid arthritis, sjogren syndrome, and SLE [23][24][25], In addition, antibodies to early diffuse antigens have also been found to be present in a high percentage of SLE and mixed connective tissue disease patients [26]. The possible participation of HCMV and EBV in the pathogenesis of JRA has been evaluated with detection of DNA by PCR; however, the results were still not conclusive [27,28], Our study was performed to explore the possible relationship between EBV-and CMV-positive rates of leukocytes and the pathogenesis of JRA and childhood SLE.…”
Section: Discussionmentioning
confidence: 99%
“…In SLE, 238 Tsai/Chiang/Kao/Hsieh Epstein-Barr Virus and Systemic Lupus erythematosus polyclonal B activation might play an important role in the pathogenic mechanism of the disease process, and abnor mal expansion of the autoreactive B cell population induced by viral infection like EBV might lead to autoimmune reac tions. Antibodies against specific EBV nuclear antigens have been related to certain autoimmune diseases such as rheumatoid arthritis, sjogren syndrome, and SLE [23][24][25], In addition, antibodies to early diffuse antigens have also been found to be present in a high percentage of SLE and mixed connective tissue disease patients [26]. The possible participation of HCMV and EBV in the pathogenesis of JRA has been evaluated with detection of DNA by PCR; however, the results were still not conclusive [27,28], Our study was performed to explore the possible relationship between EBV-and CMV-positive rates of leukocytes and the pathogenesis of JRA and childhood SLE.…”
Section: Discussionmentioning
confidence: 99%
“…12 It has been suggested that rheumatic diseases arise as a consequence of antigenic cross-reactivity of anti-EBV antibodies. [13][14][15] PM/DM is associated with a higher risk of malignancies. [16][17][18] Nasopharyngeal carcinoma (NPC) is the most common malignancy in Chinese PM/DM patients.…”
Section: Introductionmentioning
confidence: 99%
“…If EBV is indeed involved in the pathogenesis of SLE, then there must be some association between EBV infection and SLE [6-9]. Elevated titers of anti-EBV antibodies have been detected in SLE patients compared with control individuals [10-12].…”
Section: Introductionmentioning
confidence: 99%